Neurocognitive and mental health outcomes and association with quality of life among adults living with HIV: a cross-sectional focus on a low-literacy population from coastal Kenya. Issue 9 (17th September 2018) - Nyongesa, Moses Kachama; Mwangala, Patrick N; Mwangi, Paul; Kombe, Martha; Newton, Charles R J C; Abubakar, Amina A
Abstract : Objectives: Our aim was to compare the neurocognitive performance and mental health outcome of adults living with HIV on antiretroviral therapy with that of community controls, all of low literacy. Furthermore, we also wanted to explore the relationship of these outcomes with quality of life among adults living with HIV. Study design: This was a descriptive cross-sectional study. Setting: The study was conducted in Kilifi County, a region located at the Kenyan coast. Participants: The participants consisted of a consecutive sample of 84 adults living with HIV and 83 randomly selected community controls all with ≤8 years of schooling. All participants were assessed for non-verbal intelligence, verbal working memory and executive functioning. The Major Depression Inventory and a quality of life measure (RAND SF-36) were also administered. Results: Using analysis of covariance, we found no statistically significant group differences between adults living with HIV and community controls in all the neurocognitive tests except for a marginal difference in the non-verbal intelligence test (F (1, 158)=3.83, p=0.05). However, depressive scores of adults living with HIV were significantly higher than those of controls (F (1, 158)=11.56, p<0.01). Also, quality of life scores of adults living with HIV were significantly lower than those of controls (F (1, 158)=4.62, p=0.03). For the HIV-infected group, results from multivariable linear regression analysis showed that increasing depressive scores were significantly associated with poorer quality of life (β=−1.17, 95% CI −1.55 to –0.80; p<0.01). Conclusion: Our findings suggest that adults of low-literacy levels living with HIV and on antiretroviral medication at the Kenyan coast do not have significant cognitive deficits compared with their uninfected counterparts. However, their mental health, compared with that of HIV-uninfected adults, remains poorer and their quality of life may deteriorate when HIV and depressive symptoms co-occur.